Efektivitas Model Project Based Learning (PJBL) Dalam Meningkatkan Pemahaman Materi Sumber Energi Melalui Pembuatan Kincir Angin Dari Kertas Origami - Nabila Gusti Dinata; Nadia Chendria Putri; Nenti Puspita; Tri Eva Lestari; Vira Sundayu (Yayasan Darussalam Bengkulu, 2024)
This study aims to evaluate the effectiveness of the Project Based Learning (PjBL) model in improving students' understanding of energy sources in grade 5B students of SD Negeri 106 Bengkulu City through a mini windmill making project from origami. The type of research used is evaluative with a quantitative and qualitative descriptive approach. The research subjects consisted of 31 grade 5B students. Data were collected through learning outcome tests, student activity observation sheets, and project product assessments. The results showed that the implementation of the origami windmill project-based PjBL was able to improve students' conceptual understanding of energy sources, indicated by an increase in the average test score from the sufficient to good category. Student activities during the learning process also showed an increase in aspects of collaboration, creativity, and problem-solving abilities. In addition, the origami windmill project effectively helped students understand the concept of wind energy and its utilization through concrete visual representations. Thus, the PjBL model can be concluded as effective in improving students' understanding of energy sources material and supporting the development of 21st-century skills in the MI/SD learning environment. Kata kunci: Project Based Learning, evaluasi pembelajaran, sumber energi, kincir angin origami, SD/MI.